(untitled) (Bangladesh Journal of Animal Science, 2012)
The experiment was carried out to evaluate the effect of different levels of dried slurry (DS) as source of nitrogen fertilizer on yield and chemical composition of maize fodder (Zea mays). Four levels of DS (0, 10, 12 and 14 ton/ha) were applied in a Randomized Block Design (RBD). Green biomass yields was significantly higher in DS incorporated groups compared to control. The highest (P<0.01) biomass yield was observed at the application of 12 ton DS/ha. Application of 12 ton DS/ha resulted highest plant height, number of leaves and leaves area (cm2) and stem circumference of maize fodder (P<0.01). Dry matter (DM) and crude protein (CP) content of maize fodder was increased (P<0.01) with an application of 12 ton DS/ha while acid detergent fiber (ADF) and total ash contents were decreased with an increased level of DS. Organic matter (OM) and neutral detergent fiber (NDF) content of green grass were non significant for the incorporation of different levels of DS. From the results of the present study it is evident that, maize fodder can be cultivated through the application of 12 ton DS/ha for obtaining higher yield and nutrient content. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9881 BJAS 2008; 37(2): 52-57